2013
DOI: 10.1063/1.4815882
|View full text |Cite
|
Sign up to set email alerts
|

Near-field mapping of dipole nano-antenna-coupled bolometers

Abstract: The near-field characteristics of single, double, and arrays of connected dipole nano-antennas coupled to bolometers were studied by infrared scattering scanning near-field optical microscopy (s-SNOM) and analyzed by numerical simulations. Results were consistent with classical antenna theory showing the expected p phase difference across the terminals of the dipoles. However, according to the observed differences between the measurements and simulations, the symmetry of the amplitude signal appeared to be sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…5 where realized gain is defined as the ratio of the radiated power in each direction to the power of the incident beam. For the phase-ramped loops, the measured deflected angle is 23 while the phase-ramped patches have a deflected angle of 24 , which is relatively close to the calculated values of 25 for both structures. One difference between the calculated and measured beam deflection angle is that the calculation is based on values of reflected phase obtained from simulations of uniform arrays of elements while the measurement is of the phase-ramped structures having different size elements.…”
Section: -supporting
confidence: 50%
“…5 where realized gain is defined as the ratio of the radiated power in each direction to the power of the incident beam. For the phase-ramped loops, the measured deflected angle is 23 while the phase-ramped patches have a deflected angle of 24 , which is relatively close to the calculated values of 25 for both structures. One difference between the calculated and measured beam deflection angle is that the calculation is based on values of reflected phase obtained from simulations of uniform arrays of elements while the measurement is of the phase-ramped structures having different size elements.…”
Section: -supporting
confidence: 50%
“…The interfering beams are sampled with a HgCdTe (MCT) detector, using a lock-in amplifier to sample the signal at the second-harmonic of the AFM tip dither frequency. The intensity at the detector can be expressed as follows [19,22,25…”
Section: Near-field Characterizationmentioning
confidence: 99%
“…Here E scat is the field of the scattered sample beam, E ref is the field of the reference beam, φ is the phase difference between the two beams, and I b represents a background signal which is not related to either the sample signal or reference beam. The terms which do not oscillate according to φ are diminished significantly due to the use of the lock-in amplifier as well as the orthogonally polarized excitation and detection scheme [17,19,20,22,23,25]. In order to generate amplitude and phase images, several data sets are taken over the sample area of interest at different discrete reference phases.…”
Section: Near-field Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…al. reported the near-field mapping using by dipole nano-antenna-coupled bolometers at the wavelength of 10.6 µm, 6 which indicated that the nano-antenna effectively functioned. In order to improve the response performance of infrared detectors, we have also been studing the nano-antennas.…”
mentioning
confidence: 99%